Association between Nursing Spiritual Managament on Quality of Life: Meta-Analysis - Sarwoko, Sarwoko; Winarto, Eko; Sulistyowati, Nining (Journal of Health Policy and Management, 2022)
Background: Religion and spirituality play a role in coping with illness for many patients. This study examined religiousness and spiritual support in patients of diverse racial or ethnic backgrounds and associations with quality of life (QOL), treatment preferences, and advance care planning. This study aimed to analyze the association between nursing spiritual managament on quality of life based on previous studies.Subjects and Method: This study is a meta-analysis with PICO, population: inpatient. Intervention: nursing spiritual management. Comparison: without nursing spiritual management. Outcome: quality of life. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles are “Nursing” OR “Nursing Management“ AND “Nursing Spiritual Management” AND “Quality of Life” OR “QoL” AND “Multivariate”. Articles included are full-text English from 2007 to 2022. Articles were selected using a PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 8 cross-sectional study articles from Asia (Indonesia), Europe (Germany), South America (Brazil and Peru), and North America (Boston and US) were reviewed in the meta-analysis. Based on the results of the analysis, it was found that implementing of nursing spiritual management increase quality of life among patients 2.79 times compared to nurse does not implementing spiritual management (aOR= 2.79; 95% CI= 2.43 to 3.35; p< 0.001) and the result is statistically significant.Conclusion: Good hospital management increase nurse work motivation.Keywords: nursing management, spiritual points, quality of life, QoL.Correspondence:Sarwoko. Universitas Karya Husada Semarang. Jl. Kompol R. Soekanto 46, Semarang, Central Java. Email: sikoeub@gmail.com. Mobile: +62 81326925555.Journal of Health Policy and Management (2022), 07(03): 201-209https://doi.org/10.26911/thejhpm.2022.07.03.04